Respuesta :
Answer:
The answer is option 2.
Step-by-step explanation:
First, you have to make the equation into 0, by adding 6x² to both sides :
[tex]3 - 4x = - 6 {x}^{2} [/tex]
[tex]3 - 4x + 6 {x}^{2} = - 6 {x}^{2} + 6 {x}^{2} [/tex]
[tex]6 {x}^{2} - 4x + 3 = 0[/tex]
Next, you have to apply Discriminant formula, D = b² - 4ac. Given that a quadratic equation is ax² + bx + c = 0, so for this equation a represents 6, b is -4 and c is 3 :
[tex]D = {b}^{2} - 4ac[/tex]
[tex]let \: a = 6 \\ let \: b = - 4 \\ let \: c = 3[/tex]
[tex]D = {( - 4)}^{2} - 4(6)(3)[/tex]
[tex]D = 16 - 72[/tex]
[tex]D = - 56[/tex]
Answer:
-56.
Step-by-step explanation:
3 – 4x = –6x^2
6x^2 - 4x + 3 = 0
The discriminant is simply b^2 - 4ac. In this case, a = 6, b = -4, and c = 3.
(-4)^2 - 4 * 6 * 3 = 16 - (24 * 3) = 16 - 72 = -56
Hope this helps!